The Impact of Social Media Brand Community and Brand-Community Commitment on Customer Based Brand Equity - Kurnia, Pepey Riawati; Aryani, Budi; Sari, Dewi Purnama (International Research Journal of Business Studies, 2025)
In green start-up business competition, the main challenge lies in focusing on social and environmental impacts. The purpose of this study is to describe the impact of Social Media Brand Community (SMBC) on Customer-Based Brand Equity (CBBE) mediated by Brand-Community Commitment. This quantitative study uses a purposive sampling technique and the respondents of this study are members of the green start-up brand community as many as 125 respondents, data research are tested and analyzed using PLS-SEM. The findings of this study reveal that the characteristics of SMBC (shared awareness, rituals and traditions, and moral responsibility) directly affect brand awareness, perceived quality, and brand loyalty which are elements of CBBE while brand-community commitment does not affect to CBBE. To improve CBBE, it is necessary to focus on strengthening the characteristics of the brand community. The implementation of brand community in Indonesian green start-up companies has a real impact on marketing performance, especially in growing brand awareness within the community.